If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5 + -2x = -1(5x + -1x) Reorder the terms: 5 + 8x + -2x = -1(5x + -1x) Combine like terms: 8x + -2x = 6x 5 + 6x = -1(5x + -1x) Combine like terms: 5x + -1x = 4x 5 + 6x = -1(4x) Remove parenthesis around (4x) 5 + 6x = -1 * 4x Multiply -1 * 4 5 + 6x = -4x Solving 5 + 6x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + 6x + 4x = -4x + 4x Combine like terms: 6x + 4x = 10x 5 + 10x = -4x + 4x Combine like terms: -4x + 4x = 0 5 + 10x = 0 Add '-5' to each side of the equation. 5 + -5 + 10x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 10x = 0 + -5 10x = 0 + -5 Combine like terms: 0 + -5 = -5 10x = -5 Divide each side by '10'. x = -0.5 Simplifying x = -0.5
| 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) | | 2/3x=44 | | (5/9x)-(1/3)=3 | | -6r+1=-7r+20 | | 30+3x=-(3x+6) | | 3(x-4)=4x+1 | | -7-9k=7-7k | | =2z^2+13z+15 | | (2/3x)+(4/3)=(-4/3) | | 3(x-2)=4x-2-2x+3 | | 3(2x-x)=18-1 | | 8-9x-2=-40+6x-14 | | -28-6y=2(-6y+1) | | x^2/5=32 | | y+(y-50)=180 | | =4v*3v^4u^6*2u^7 | | -4x-13=6x+17 | | 3+c+6= | | 9+4x=3(x+4) | | 4-6m=(3m+14)-2(3m+5) | | 1.2t+3.4=-1.0 | | 6y+14=-7-y | | 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 |